Volume 12: Wind Energy 2020
DOI: 10.1115/gt2020-15705
|View full text |Cite
|
Sign up to set email alerts
|

Aeromechanical Analysis of a Complete Wind Turbine Using Nonlinear Frequency Domain Solution Method

Abstract: The high-fidelity computational fluid dynamics (CFD) simulations of a complete wind turbine model usually require significant computational resources. It will require much more resources if the fluid-structure interactions between the blade and the flow are considered, and it has been the major challenge in the industry. The aeromechanical analysis of a complete wind turbine model using a high-fidelity CFD method is discussed in this paper. The distinctiveness of this paper is the application of the nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They found that the inlet wakes have substantial effect on wind turbine aerodynamics and separation point. In another numerical study, Naung et al [2,3] utilized the frequency-domain method to predict the forced response and flutter instability over the wind turbine blades. They concluded that by using the newly designed model, the computation time can be reduced by order of 2 compared to the other models.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the inlet wakes have substantial effect on wind turbine aerodynamics and separation point. In another numerical study, Naung et al [2,3] utilized the frequency-domain method to predict the forced response and flutter instability over the wind turbine blades. They concluded that by using the newly designed model, the computation time can be reduced by order of 2 compared to the other models.…”
Section: Introductionmentioning
confidence: 99%